Does Pooling Really Matter? An Evaluation on Gait Recognition - dos Santos, Claudio Filipi Goncalves; Moreira, Thierry Pinheiro [UNESP]; Colombo, Danilo; Papa, João Paulo [UNESP] (Springer Nature, 2019)
Most Convolutional Neural Networks make use of subsampling layers to reduce dimensionality and keep only the most essential information, besides turning the model more robust to rotation and translation variations. One of the most common sampling methods is the one who keeps only the maximum value in a given region, known as max-pooling. In this study, we provide pieces of evidence that, by removing this subsampling layer and changing the stride of the convolution layer, one can obtain comparable results but much faster. Results on the gait recognition task show the robustness of the proposed approach, as well as its statistical similarity to other pooling methods.
Keywords: Convolutional Neural Networks; Deep learning; Gait recognition